Q. 524.0( 4 Votes )

Fill in the blanks to make the statements true.

23 × (–99) = ______× (–100 + _______) = 23 × _________+ 23 ×1

Answer :

First case:


23 × (–99) = ______× (–100 + _______)


= 23 × (-100 + 1)


Second case:


23 × (–99) =23 × _________+ 23 ×1


=23 × 100+ 23 ×1


(In first case we adjust to get the value of the question and in the second one distribution law is applied)


Thus the blank spaces are 1 and 100.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.